Wave-absorbing heat-dissipating member and application thereof in electronic device
Patent Information
- Application Number
- CN202310418168.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-04-14
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2043-04-14
AI Technical Summary
In existing technologies, the functions of absorbing waves and dissipating heat are separated, which requires electronic devices to be equipped with both absorbing and dissipating components, resulting in a large space occupation and hindering integration and miniaturization.
A wave-absorbing and heat-dissipating component is designed using composite magnetic materials and structural design, including porous graphene ellipsoids and zinc sulfide nanomaterials. The complementary filling of the serrated protrusion structure achieves the compatibility of wave absorption and heat dissipation.
It achieves both excellent wave absorption and heat dissipation performance in electronic devices, reduces space occupation, and is conducive to the integration and miniaturization of electronic devices.
Smart Images

Figure CN116456706B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of electromagnetic wave absorbing materials technology, and in particular to wave absorbing heat sinks and their applications in electronic devices. Background Technology
[0002] The massive data traffic in the 5G era places higher demands on electronic devices such as chips and antennas in communication terminals. On the one hand, the significantly increased power consumption of devices has led to a sharp increase in the heat generated by electronic devices. On the other hand, with the increase in integration and the reduction in size, electromagnetic radiation interference is inevitable.
[0003] However, in practical applications, the functions of absorbing waves and dissipating heat are often separate. In electronic devices that require both absorbing waves and dissipating heat, both absorbing and dissipating components need to be configured simultaneously. The absorbing components generally use shielding materials, such as shielding covers, while the dissipating components generally use heat dissipation sheet metal parts, heat dissipation pads, etc. The absorbing and dissipating components themselves occupy a lot of space, which is not conducive to the integration and miniaturization of electronic devices. Summary of the Invention
[0004] Therefore, it is necessary to provide a wave-absorbing heat sink and its application in electronic devices to address the above-mentioned technical problems. The wave-absorbing heat sink has both excellent wave absorption and heat dissipation performance. When applied to electronic devices, it greatly reduces the space occupied while taking into account both heat dissipation and wave absorption, which is conducive to the integration and miniaturization of electronic devices.
[0005] The present invention provides a wave-absorbing heat dissipation component, including a heat dissipation component and a wave-absorbing component stacked on the heat dissipation component. The surface of the heat dissipation component has a first serrated protrusion structure distributed at intervals, and the wave-absorbing component has a second serrated protrusion structure that is complementary to and fills the first serrated protrusion structure.
[0006] The material of the absorbing element is a composite magnetic material and a coagulant. The composite magnetic material includes a composite material composed of porous graphene ellipsoids and zinc sulfide nanomaterials, and an organic insulating material coated on the surface of the composite material. In the composite material, multiple porous graphene ellipsoids are arranged in an orderly manner to form a graphene group, and the zinc sulfide nanomaterials are fused into the graphene group.
[0007] In one embodiment, the vertical height h of the second serrated protrusion structure is 1.4mm-2.1mm, and the tooth tip spacing d is 1.4mm-2.1mm.
[0008] In one embodiment, the cross-section of the second serrated protrusion structure is an isosceles triangle.
[0009] In one embodiment, the composite magnetic material has a mass fraction of 40%-50% in the absorbing element.
[0010] In one embodiment, the porous graphene ellipsoids in the graphene group are arranged in a three-dimensional array.
[0011] In one embodiment, the porous graphene ellipsoid has an equatorial radius of 100nm-120nm and a polar radius of 200nm-250nm.
[0012] In one embodiment, the pore size of the porous graphene ellipsoid is 14nm-25nm.
[0013] In one embodiment, the ratio of the particle size of the zinc sulfide nanomaterial to the pore size of the porous graphene ellipsoid is 1:8 to 1:12.
[0014] In one embodiment, the mass ratio of the zinc sulfide nanomaterial to the graphene group in the composite magnetic material is 1:3-1:5.
[0015] The present invention also provides an application of the aforementioned wave-absorbing heat sink in electronic devices.
[0016] This invention, through the selection of materials and the control of the structure in composite magnetic materials, enables the absorption bandwidth of the composite magnetic materials to cover 20MHz-1.2GHz, with an insertion loss of approximately 25dB, exhibiting the advantages of adjustable absorption bandwidth and strong absorption performance. Furthermore, by designing the structure of the absorbing device made from it, the absorbing device achieves good shielding performance in the 30MHz-6.6GHz frequency band, with an insertion loss of 20dB-30dB.
[0017] Furthermore, by combining the absorbing component with the heat dissipation component, the absorbing and heat dissipation component can have both excellent absorbing and heat dissipation performance. It can be applied to electronic devices with high heat dissipation requirements, improve the heat dissipation performance of electronic devices and suppress electromagnetic interference. It can also be used to isolate crosstalk between signals and avoid spatial coupling of inductive devices. This solves the problem of incompatibility between absorbing and heat dissipation components, greatly reduces space, and is conducive to the integration and miniaturization of electronic devices. Attached Figure Description
[0018] Figure 1 This is a schematic diagram of the structure of the wave-absorbing heat dissipation component of the present invention;
[0019] Figure 2 This is a high-magnification scanning electron microscope image of the graphene group obtained in Example 1;
[0020] Figure 3 This is a high-magnification scanning electron microscope image of the composite magnetic material prepared in Example 1.
[0021] In the figure, 10 is a heat sink; 20 is a wave absorber; 101 is the first serrated protrusion structure; and 201 is the second serrated protrusion structure. Detailed Implementation
[0022] To facilitate understanding of the present invention, it will be described in more detail below. However, it should be understood that the present invention can be implemented in many different forms and is not limited to the embodiments or examples described herein. Rather, these embodiments or examples are provided to make the disclosure of the present invention more thorough and complete.
[0023] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. The terminology used herein in the specification of this invention is for the purpose of describing particular embodiments or examples only and is not intended to limit the invention. The optional scope of the term "and / or" as used herein includes any one of two or more of the related listed items, as well as any and all combinations of the related listed items, including any two related listed items, any more related listed items, or a combination of all related listed items.
[0024] like Figure 1 As shown, a wave-absorbing heat sink according to an embodiment of the present invention includes a heat sink 10 and a wave-absorbing component 20 superimposed on the heat sink 10. The surface of the heat sink 10 has a first serrated protrusion structure 101 spaced apart, and the wave-absorbing component 20 has a second serrated protrusion structure 201 that is complementary to and filled with the first serrated protrusion structure 101.
[0025] The material of the absorbing component 20 is a composite magnetic material and a coagulant. The composite magnetic material includes a composite material composed of porous graphene ellipsoids and zinc sulfide nanomaterials, and an organic insulating material coated on the surface of the composite material. In the composite material, multiple porous graphene ellipsoids are arranged in an orderly manner to form a graphene group, and the zinc sulfide nanomaterials are fused into the graphene group.
[0026] Specifically, the zinc sulfide nanomaterials are integrated into the graphene group in the following ways: zinc sulfide nanomaterials are attached to the surface of at least a portion of the porous graphene ellipsoids, and zinc sulfide nanomaterials are filled in at least a portion of the gaps in the graphene group; furthermore, when the particle size of the zinc sulfide nanomaterials is smaller than the pore size of the porous graphene ellipsoids, the integration of the zinc sulfide nanomaterials into the graphene group also includes the presence of zinc sulfide nanomaterials within the channels of at least a portion of the porous graphene ellipsoids. Of course, the specific integration method will not have a substantial impact on the wave absorption performance.
[0027] Different structural types and materials exhibit varying electromagnetic wave conversion capabilities. In this invention, graphene and zinc sulfide are combined in terms of materials. Structurally, graphene particles are bonded together with binders such as phenolic resin to form porous graphene ellipsoids, which are then arranged in an orderly manner to form graphene clusters. Zinc sulfide nanomaterials are integrated into these graphene clusters in various ways. This allows for faster and more efficient conversion of electromagnetic waves into heat energy. Furthermore, graphene's excellent thermal conductivity enables rapid heat transfer, resulting in superior absorption performance of the composite magnetic material across a wide frequency range. Specifically, the absorption bandwidth of the composite magnetic material covers 20MHz-1.2GHz, with an insertion loss of approximately 25dB.
[0028] Therefore, by designing the structure of the absorbing component made from it, the absorbing component has good shielding performance in the 30MHz-6.6GHz frequency band, with an insertion loss of 20dB-30dB.
[0029] In addition, graphene has excellent thermal conductivity, which makes the wave-absorbing component 20 made of composite magnetic materials have excellent thermal conductivity. Furthermore, it is combined with the heat sink 10 in a complementary manner with a serrated protrusion structure, so that the wave-absorbing heat sink has both excellent wave absorption and heat dissipation performance. It can be applied to electronic devices with high heat dissipation requirements, improve the heat dissipation performance of electronic devices and suppress electromagnetic interference. It can also be used to isolate crosstalk between signals and avoid spatial coupling of inductive devices, thereby solving the problem of incompatibility between wave-absorbing components and heat sink components, greatly reducing space, and facilitating the integration and miniaturization of electronic devices.
[0030] To further optimize the wave absorption performance of the wave-absorbing heat sink, the structure of the composite magnetic material and the structure of the wave-absorbing component 20 can be further optimized.
[0031] For example, in composite magnetic materials, when multiple porous graphene ellipsoids are arranged in an orderly manner to form a graphene group, the porous graphene ellipsoids are arranged in a three-dimensional array; and / or, the equatorial radius of the porous graphene ellipsoids is 100nm-120nm, and the polar radius is 200nm-250nm; and / or, the pore size of the porous graphene ellipsoids is 14nm-25nm, and the ratio of the particle size of the zinc sulfide nanomaterial to the pore size of the porous graphene ellipsoids is 1:8-1:12.
[0032] For example, in the absorbing component 20, the vertical height h of the second serrated protrusion structure 201 is 1.4mm-2.1mm, and the tooth tip spacing d is 1.4mm-2.1mm; and / or, the cross section of the second serrated protrusion structure 201 is an isosceles triangle.
[0033] To further optimize the wave absorption performance of the wave-absorbing heat dissipation component, the mass ratio of porous graphene ellipsoids to zinc sulfide nanomaterials in the composite magnetic material can be further optimized. In one embodiment, the mass ratio of zinc sulfide nanomaterials to graphene groups in the composite magnetic material is 1:3-1:5; and / or, the mass fraction of the composite magnetic material in the wave-absorbing component 20 can be optimized. In one embodiment, the mass fraction of the composite magnetic material in the wave-absorbing component 20 is 40%-50%.
[0034] In the microwave absorbing component 20, the choice of coagulant material will not affect its microwave absorption effect. The present invention does not restrict the choice of coagulant. Preferably, the coagulant is selected from propylene glycol, disodium ethylenediaminetetraacetate, disodium stannous citrate, gluconate-δ-lactone and insoluble polyvinylpyrrolidone, etc.
[0035] The present invention does not limit the selection of the heat sink 10, which can be a heat sink pad, a sheet metal part, a thermally conductive silicone, a thermally conductive silicone grease, etc. Among them, when the heat sink 10 is preferably a heat sink pad, a thermally conductive silicone, a thermally conductive silicone grease, etc., the heat sink obtained in conjunction with the wave absorbing component 20 has excellent flexibility and ductility. At the same time, due to the low density of graphene and zinc sulfide, and the use of organic insulating materials to insulate the composite material, the wave absorbing heat sink also has the advantages of being lightweight and electrically insulating.
[0036] When composite materials are insulated using organic insulating materials, the organic insulating materials can partially coat the surface of the composite material or completely coat the composite material. Preferably, the organic insulating materials completely coat the composite material. The organic insulating materials are preferably block polymers, such as ethylene oxide and propylene oxide block copolymer ethers. Coating with organic insulating materials can also make the bonding of the composite material more stable.
[0037] In one embodiment, the raw materials for preparing the heat sink 10, by mass fraction, include: 15%-20% vinyl silicone oil, 0.5%-1.9% hydrogen-containing silicone oil, 0.01%-0.55% catalyst, 0.2%-0.51% inhibitor, and the balance being thermally conductive powder. The catalyst is selected from at least one of chloroplatinic acid, chloroplatinic acid-isopropanol complex, and chloroplatinic acid-divinyltetramethyldisiloxane complex; the inhibitor is selected from at least one of ethynylcyclohexanol, 2-phenyl-3-butyn-2-ol, 2-methyl-3-butynyl-2-ol, 3-methyl-1-ethynyl-3-ol, 3,5-dimethyl-1-ethynyl-3-ol, and 3-methyl-1-dodecynyl-3-ol; the hydrogen-containing silicone oil has a viscosity of 5 mm. 2 / S-500mm 2 / S, hydrogen content is 0.01%-1.2%; the viscosity of vinyl silicone oil is 60 mm. 2 / S-160mm 2 / S, with a vinyl content of 0.2%-3.5%; the thermally conductive powder is selected from at least one of alumina, aluminum, zinc oxide, aluminum hydroxide, magnesium hydroxide, boron nitride, ceramics, etc., with a particle size of 0.1μm-100μm.
[0038] Therefore, the wave-absorbing heat dissipation component provided by the present invention has both excellent wave absorption and heat dissipation performance, which can solve the problem of incompatibility between traditional wave absorption and heat dissipation.
[0039] The fabrication method of the wave-absorbing heat sink of the present invention is not limited, and any method can be used for fabrication, as long as the structure and materials meet the above-mentioned conditions of the present invention, the desired effect can be achieved. For example, a heat sink 10 with a first serrated protrusion structure 101 can be fabricated first, and then the wave-absorbing component 20 can be fabricated using the heat sink 10 as a mold to obtain the wave-absorbing heat sink; or a wave-absorbing component 20 with a second serrated protrusion structure 201 can be fabricated first, and then the heat sink 10 can be fabricated using the wave-absorbing component 20 as a mold to obtain the wave-absorbing heat sink; or a heat sink 10 with a first serrated protrusion structure 101 and a wave-absorbing component 20 with a second serrated protrusion structure 201 can be fabricated separately, and then stacked to obtain the wave-absorbing heat sink.
[0040] In one embodiment, the method for fabricating the wave-absorbing heat sink includes the following steps:
[0041] Vinyl silicone oil, hydrogen-containing silicone oil, catalyst, inhibitor and thermally conductive powder are mixed according to the formula to obtain heat dissipation slurry. Composite magnetic material is mixed into coagulant according to the formula to obtain microwave absorbing slurry.
[0042] Then, a serrated template is selected, and the heat dissipation slurry is filled into the template. After curing, a heat dissipation component 10 with a first serrated protrusion structure 101 is obtained. Then, the heat dissipation component 10 is sealed around its perimeter, and a wave-absorbing slurry is added therein. After curing, a wave-absorbing heat dissipation component is obtained.
[0043] Alternatively, a serrated template can be selected, the microwave absorbing slurry can be filled into the template, and after curing, a microwave absorbing component 20 with a second serrated protrusion structure 201 can be obtained. Then, the microwave absorbing component 20 can be sealed around its perimeter, and a heat dissipation slurry can be added therein. After curing, a microwave absorbing heat dissipation component can be obtained.
[0044] It should be noted that when preparing microwave absorbing slurry, the composite magnetic material can be dispersed in water first, and then the coagulant can be added.
[0045] Furthermore, the present invention does not limit the preparation method of composite magnetic materials; any preparation method can be used to obtain them, as long as the structure and materials meet the above-mentioned conditions of the present invention, the desired effect can be achieved.
[0046] In one embodiment, the preparation method of the composite magnetic material includes the following steps: preparing graphene groups using a colloidal crystal template method, then mixing the graphene groups with zinc sulfide nanomaterials, adding organic insulating materials, heating to a viscous state, and then cooling to obtain the composite magnetic material.
[0047] The specific steps for preparing graphene groups using the colloidal crystal template method include: preparing a first formulation by mixing graphene with water, then mixing the first formulation with a binder to form a second formulation, then adding the second formulation to a colloidal crystal template and heating it under an inert atmosphere, and then cooling it under a reducing atmosphere to obtain graphene groups.
[0048] The graphene to water mass ratio is 1:2-1:4, the graphene to binder mass ratio is 10:1-10:3, the binder is preferably a resin-based binder, such as phenolic resin, the graphene to colloidal crystal mass ratio is 6:1-12:1, the colloidal crystal template is selected from polymethyl methacrylate colloidal crystal template, the heating temperature is preferably 180℃-220℃, the heating time is preferably 20h-28h, the inert atmosphere is selected from nitrogen, argon, etc., and the reducing atmosphere is selected from carbon monoxide, hydrogen, etc.
[0049] To further improve the stability of graphene, a reducing catalyst, such as SnCl2 or FeCl2, can be added to the first formulation. The mass ratio of graphene to the reducing catalyst is 1:1 to 2:1. Then, the mixture is heated in an inert gas and cooled in a reducing atmosphere to obtain a more stable first formulation. The preferred heating temperature is 220℃ to 280℃, and the preferred heating time is 4h to 8h.
[0050] The present invention also provides the application of the aforementioned absorbing heat sink in electronic devices. The absorbing heat sink has both excellent absorbing and heat dissipation performance, which can effectively improve the heat dissipation performance of electronic devices and suppress electromagnetic interference. It can also be used to isolate crosstalk between signals and avoid spatial coupling of inductive devices, thereby solving the problem of incompatibility between absorbing components and heat dissipation components, greatly reducing space, and facilitating the integration and miniaturization of electronic devices.
[0051] The following specific embodiments will further illustrate the microwave absorbing heat sink and its application in electronic devices.
[0052] Example 1
[0053] Graphene powder was added to water at a mass ratio of 1:3 and mixed. Then SnCl2 was added, with a mass ratio of SnCl2 to graphene powder of 1:1. The mixture was placed in an argon atmosphere and heated at 250°C for 6 hours. Then it was cooled in a CO atmosphere to obtain the first formulation.
[0054] The first formulation and phenolic resin are mixed to obtain the second formulation, wherein the mass ratio of graphene powder to phenolic resin is 10:2.
[0055] The second formulation was added to polymethyl methacrylate colloidal crystals at a mass ratio of graphene to polymethyl methacrylate colloidal crystals of 8:1. The mixture was then placed in an argon atmosphere and heated at 200°C for 24 hours, followed by cooling in a carbon monoxide atmosphere to obtain the desired product. Figure 2 The graphene group shown is composed of porous graphene ellipsoids arranged in a three-dimensional array. The equatorial radius of the porous graphene ellipsoids is 100 nm, the polar radius is 210 nm, and the pore size is 18 nm.
[0056] Graphene groups and zinc sulfide nanomaterials with a particle size of 1.8 nm were added to water at a mass ratio of 4:1 and stirred to mix. Then, ethylene oxide and propylene oxide block copolymer ether were added, and the mixture was heated to 150°C in an argon atmosphere until it reached a viscous state. After cooling, the mixture was obtained as shown in the figure. Figure 3 The composite magnetic material shown.
[0057] The composite magnetic material is dispersed in water, and then propylene glycol is added to obtain the microwave absorbing slurry, wherein the mass ratio of the composite magnetic material to propylene glycol is 3:4.
[0058] By mass fraction, 18% vinyl silicone oil (viscosity 100 mm) 2 / S, vinyl content of 0.3%, 1% hydrogen-containing silicone oil (viscosity of 100mm) 2 The heat dissipation slurry was obtained by uniformly mixing boron nitride (with a hydrogen content of 0.5%), 0.3% chloroplatinic acid, 0.3% ethynylcyclohexanol, and the balance boron nitride (particle size of 15 μm) in a double planetary mixer.
[0059] A serrated template (with a vertical height h and a tooth tip distance d of 1.5 mm) is selected. The heat dissipation slurry obtained above is filled into the serrated template. The surface is then smoothed with a brush. After cooling, a heat dissipation component with a first serrated protrusion structure is obtained. The heat dissipation component is then sealed around its perimeter, and the microwave absorbing slurry obtained above is added. The surface is then smoothed with a brush. After cooling, a microwave absorbing heat dissipation component is obtained.
[0060] Example 2
[0061] Example 2 was carried out in accordance with Example 1, except that the mass ratio of graphene group to zinc sulfide nanomaterial was 5:1.
[0062] Example 3
[0063] Example 3 was carried out in accordance with Example 1, except that the mass ratio of graphene group to zinc sulfide nanomaterial was 3:1.
[0064] Example 4
[0065] Example 4 was carried out in accordance with Example 1, except that the second formulation was added to polymethyl methacrylate colloidal crystals and heated at 180°C for 24 hours. The equatorial radius of the porous carbon rod was 100 nm, the polar radius was 200 nm, and the pore diameter was 14 nm. In addition, the particle size of the zinc sulfide nanomaterial was 1.7 nm.
[0066] Example 5
[0067] Example 5 was carried out in accordance with Example 1, except that the second formulation was added to polymethyl methacrylate colloidal crystals and heated at 220°C for 22 hours. The equatorial radius of the porous carbon rod was 110 nm, the polar radius was 210 nm, and the pore diameter was 17 nm. In addition, the particle size of the zinc sulfide nanomaterial was 1.7 nm.
[0068] Example 6
[0069] Example 6 was carried out in accordance with Example 1, except that the second formulation was added to polymethyl methacrylate colloidal crystals and heated at 220°C for 24 hours. The equatorial radius of the porous carbon rod was 120 nm, the polar radius was 220 nm, and the pore diameter was 22 nm. In addition, the particle size of the zinc sulfide nanomaterial was 2 nm.
[0070] Example 7
[0071] Example 7 is carried out in accordance with Example 1, except that the vertical height h of the saw teeth is 1.4 mm and the tooth tip distance d is 1.4 mm.
[0072] Example 8
[0073] Example 8 is carried out in accordance with Example 1, except that the vertical height h of the saw teeth is 1.6 mm and the tooth tip distance d is 1.6 mm.
[0074] Example 9
[0075] Example 9 was carried out with reference to Example 1, except that the vertical height h of the saw teeth was 2.1 mm and the tooth tip distance d was 2.1 mm.
[0076] Example 10
[0077] Example 10 was carried out in accordance with Example 1, except that the mass ratio of the composite magnetic material to propylene glycol was 1:1.
[0078] Comparative Example 1
[0079] Comparative Example 1 was carried out with reference to Example 1, except that the absorbing element has a spaced hemispherical protrusion structure with a diameter of 1.5 mm, and the heat dissipation element has a protrusion structure that is complementary to the absorbing element.
[0080] Comparative Example 2
[0081] Comparative Example 2 is carried out with reference to Example 1, except that the absorbing component has a spaced square protrusion structure with a vertical height and spacing of 1.5 mm, and the heat dissipation component has a protrusion structure that is complementary to the absorbing component.
[0082] Comparative Example 3
[0083] Comparative Example 3 was carried out in accordance with Example 1, except that the second formulation was added to polymethyl methacrylate colloidal crystals and heated at 150°C for 24 hours to obtain a three-dimensional arrangement of spherical graphene groups.
[0084] Comparative Example 4
[0085] Comparative Example 4 was carried out in accordance with Example 1, except that the second formulation was added to polymethyl methacrylate colloidal crystals and heated at 190°C for 18 hours to obtain a three-dimensional arrangement of rod-shaped graphene groups.
[0086] Comparative Example 5
[0087] Comparative Example 5 was carried out in accordance with Example 1, except that carbon nanotubes were used instead of graphene to obtain a group of carbon nanotubes arranged in three dimensions of porous carbon nanotube ellipsoids.
[0088] The thermal conductivity and wave absorption performance of the wave-absorbing heat sinks obtained in Examples 1-11 and Comparative Examples 1-5 were tested. The test methods are shown below, and the test results are shown in Table 1.
[0089] Thermal conductivity: Measured using the steady-state heat flow method, in accordance with GB / T8722.
[0090] Absorption performance: Refer to GB / T32596 to test absorption bandwidth and insertion loss.
[0091] Table 1
[0092]
[0093] The technical features of the above embodiments can be combined in any way. For the sake of brevity, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0094] The embodiments described above are merely illustrative of several implementations of the present invention, and while the descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the invention patent. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these all fall within the protection scope of the present invention. Therefore, the protection scope of this invention patent should be determined by the appended claims.
Claims
1. A wave-absorbing heat dissipation component, characterized in that, The device includes a heat sink and a wave absorber stacked on the heat sink. The surface of the heat sink has a first serrated protrusion structure distributed at intervals, and the wave absorber has a second serrated protrusion structure that is complementary to and fills the first serrated protrusion structure. The absorber is made of a composite magnetic material and a coagulant. The composite magnetic material comprises a composite material consisting of porous graphene ellipsoids and zinc sulfide nanomaterials, and an organic insulating material coating the surface of the composite material. In the composite material, multiple porous graphene ellipsoids are arranged in an orderly manner to form a graphene cluster. The zinc sulfide nanomaterials are fused into the graphene cluster. The mass ratio of the zinc sulfide nanomaterials to the graphene cluster is 1:3 to 1:
5. The equatorial radius of the porous graphene ellipsoids is 100nm-120nm, the polar radius is 200nm-250nm, and the pore size of the porous graphene ellipsoids is 14nm-25nm.
2. The wave-absorbing heat dissipation component according to claim 1, characterized in that, The vertical height h of the second serrated protrusion structure is 1.4mm-2.1mm, and the tooth tip spacing d is 1.4mm-2.1mm.
3. The wave-absorbing heat dissipation component according to claim 1, characterized in that, The cross-section of the second sawtooth protrusion structure is an isosceles triangle.
4. The wave-absorbing heat dissipation component according to any one of claims 1-3, characterized in that, The coagulant is selected from propylene glycol, disodium ethylenediaminetetraacetate, disodium stannous citrate, glucono-δ-lactone, and insoluble polyvinylpyrrolidone.
5. The wave-absorbing heat dissipation component according to any one of claims 1-3, characterized in that, The heat dissipation component is selected from heat dissipation pads, sheet metal parts, thermally conductive silicone or thermally conductive ester.
6. The wave-absorbing heat dissipation component according to any one of claims 1-3, characterized in that, The composite magnetic material has a mass fraction of 40%-50% in the absorbing component.
7. The wave-absorbing heat dissipation component according to any one of claims 1-3, characterized in that, In the graphene group, the porous graphene ellipsoids are arranged in a three-dimensional array.
8. The wave-absorbing heat dissipation component according to any one of claims 1-3, characterized in that, The ratio of the particle size of the zinc sulfide nanomaterial to the pore size of the porous graphene ellipsoid is 1:8 to 1:
12.
9. The wave-absorbing heat dissipation component according to any one of claims 1-3, characterized in that, The organic insulating material is selected from ethylene oxide or propylene oxide block copolymer ether.
10. The application of a wave-absorbing heat sink as described in any one of claims 1-9 in an electronic device.
Citation Information
Patent Citations
Regulable microporous wave-absorbing metamaterial and preparation method and application
CN110205096A
Three-dimensional ordered porous graphene wave-absorbing material and preparation method thereof
CN113511648A
Thermally-conductive shielding organosilicon material and preparation method therefor
WO2020107599A1
